مشكل العطف في القرآن الكريم – عرض وتوجيه - - شكيمة, عبد القادر (جامعة الوادي - University of Eloued, 2023)
هذا مقال بعنوان: مشكل العطف في القرآن الكريم – عرض وتوجيه –، إشكاليته: ما هي المواضع من القرآن الكريم التي أشكلت بسبب مخالفتها لظواهر قواعد اللغة في باب العطف، وهل يمكن توجيهها والاحتجاج لها؟ فكان الجواب أن كان البحث فيه باستقراء القرآن الكريم واستخراج كل معطوف ومعطوف عليه وحرف عطف خالف فيما يتبادر للذهن القواعد المتعلقة بباب العطف، ثم توجيهها بالاستناد لقواعد اللغة والتفسير وكلام العلماء. والمشكلاتُ المدروسة تتعلق بحروف العطف، وعطف الأفعال على الأفعال، والأسماء على الأسماء، والأفعال على الأسماء، والأسماء على الأفعال، وبعد الدراسة خلصت إلى أن كل مشكل مثار له جوابه وتوجييهه، وأن القرآن كتاب محفوظ منه تستمد قواعد اللغة؛ فهو الأصل لها لا هي الأصل له. Abstract: This article is entitled “The Problem of Conjunctions in the Holy Quran”; presentation and guidance, Its problem: What are the places in the Holy Quran that were formed because of their violation of rules of conjunctions, and can they be directed and argued with? The answer was that the research was by extrapolating the Holy Qur’an and extracting every conjunction that violated what comes to mind the rules related to conjunctions, then directing them based on the rules of language, interpretation and the words of scholars. The studied problems are related to conjunctions, verbs to verbs, nouns to nouns, verbs to nouns, and nouns to verbs. After the study, I concluded that every problem raised has its answer and direction, and that the Quran is a preserved book from which the grammar of language is derived; the Quran is its origin.
مقال
Keywords: القرآن الكريم، العطف، المشكل، التوجيه.